Предмет: Математика,
автор: Alekseilol
Пожалуйста срочно надо
Приложения:
Ответы
Автор ответа:
0
пишу сразу действия и решения
а)1(x+3)^2 : xx2-9=1(x+3)^2 * (x-3)(x+3)x=x-3x(x+3)
2)(x-3x(x+3))-(x-9x2-9)=(x-3x(x+3)- (x-9(x+3)(x-3))=(x-3)^2x(x-3)(x+3) - (x(x-9)x(x-3)(x+3))=x2-6x-9-x2+9xx(x-3)(x+3)=3x-9x(x-3)(x+3)=3(x-3)x(x-3)(x+3)=3x(x+3)
б)1)aa2-4*(a+2)^2a=a(a-2)(a+2) * (a+2)^2a=a+2a-2
2)(a+6a2-4)+ (a+2a-2)=(a+6(a-2)(a+2)+(a-2a+2)=a+6+(a-2)^2(a-2)(a+2)=a+6+a2-4a+4(a-2)(a+2)=a2-3a+10(a-2)(a+2)
а)1(x+3)^2 : xx2-9=1(x+3)^2 * (x-3)(x+3)x=x-3x(x+3)
2)(x-3x(x+3))-(x-9x2-9)=(x-3x(x+3)- (x-9(x+3)(x-3))=(x-3)^2x(x-3)(x+3) - (x(x-9)x(x-3)(x+3))=x2-6x-9-x2+9xx(x-3)(x+3)=3x-9x(x-3)(x+3)=3(x-3)x(x-3)(x+3)=3x(x+3)
б)1)aa2-4*(a+2)^2a=a(a-2)(a+2) * (a+2)^2a=a+2a-2
2)(a+6a2-4)+ (a+2a-2)=(a+6(a-2)(a+2)+(a-2a+2)=a+6+(a-2)^2(a-2)(a+2)=a+6+a2-4a+4(a-2)(a+2)=a2-3a+10(a-2)(a+2)
Похожие вопросы
Предмет: Алгебра,
автор: nastyja67
Предмет: Математика,
автор: kakharmanovanarmina
Предмет: Химия,
автор: Gggg000i
Предмет: Математика,
автор: Yanatalinca
Предмет: Биология,
автор: OLESAIY